The best loved poems of the American people - Felleman, Hazel (New York : Doubleday, 1936)
Contains over 575 of the most frequently requested poems in America, divided by subject and indexed by authors and first lines.
Adult
Adult
Wilson's Public Library
Library Journal
Booklist
Keywords: English poetry; American poetry; English poetry -- Collections; American poetry -- Collections